Moral Paradox And Legal Pragmatism: A Multi-Analysis Of The Cooperating Accomplice (Justice Collaborator) In Indonesia - Yudhi Hertanto; Ibrahim Fajri (JURNAL MAHASISWA YUSTISI, 2026)
The institution of the cooperating accomplice, universally known as the Justice Collaborator (JC), represents a crucial legal breakthrough in combating extraordinary crimes such as corruption, money laundering, and organized crime in Indonesia. However, its implementation triggers intense doctrinal debates because it entails granting legal incentives to criminal perpetrators. This study aims to analyze the existence and effectiveness of the JC through an interdisciplinary approach that integrates dogmatic-juridical, socio-legal, and philosophical perspectives. Employing a normative-empirical (socio-legal) research method alongside statutory, conceptual, and contemporary case approaches, this article dissects the structural tensions inherent in law enforcement. Juridically, the study reveals that regulatory overlaps between SEMA No. 4 of 2011 and Law No. 31 of 2014 generate operational uncertainty regarding the criteria for identifying the "main perpetrator." Sociologically, the JC institution directly collides with deviant subcultures and the code of silence (omertà) within criminal syndicates, wherein perpetrators experience an identity shift from transgressive actors to state collaborators driven by rational choice calculations (rational choice theory). Philosophically, a profound antinomy persists between absolute retributive justice, which demands proportional retribution, and legal utilitarianism, which prioritizes broader public utility. This study concludes that strengthening the JC institution requires the harmonization of sectoral regulations, more accommodative witness protective measures by the LPSK, and consistent judicial recognition to pierce the veil of corporate secrecy and corrupt bureaucracies within the contemporary landscape of national law enforcement.